The mathematics of knots: theory and application - Banagl, Markus; Vogel, Denis (Springer-Verlag Berlin Heidelberg, 2011)
Preface -- 1 Knots, Singular Embeddings, and Monodromy -- 2 Lower Bounds on Virtual Crossing Number and Minimal Surface Genus -- 3 A Survey of Twisted Alexander Polynomials -- 4 On Two Categorifications of the Arrow Polynomial for Virtual Knots -- 5 An Adelic Extension of the Jones Polynomial -- 6 Legendrian Grid Number One Knots and Augmentations of their Differential Algebras -- 7 Embeddings of Four-Valent Framed Graphs into 2-Surfaces -- 8 Geometric Topology and Field Theory on 3-Manifolds -- 9 From Goeritz Matrices to Quasi-Alternating Links -- 10 An Overview of Property 2R -- 11 DNA, Knots and Tangles.
Description based upon print version of record
Keywords: Konferenzschrift -- 2008 -- Heidelberg; Knotentheorie